Contingências da violência em um território estigmatizado. - Paiva, Luiz Fábio Silva (2007)
This dissertation deals with issues related to urban violence as found in the district of Bom Jardim which is considered by public security institutions in the State of Ceara as one of the most violent and dangerous area in the city of Fortaleza. This work aims at understanding how dwellers of this district react to stigmas that have originated from the idea that the place is violent and dangerous, and at the same time having to deal with objective daily situations related to violence and crime. The public investigated was formed mostly by dwellers classified as low income workers. They live in an environment plagued by structural problems which, according to their apprehension, contribute to the dissemination of criminal practices such as thefts and armed robbery against the people in Bom Jardim. Among those problems, it is listed the lacking of an efficient public security system which could prevent violence, and react immediately to contain the diffuse spreading of criminal practice. It was observed that Bom Jardim is a place marked by strong territorial differentiations arising from a disorderly occupational process of urban space. This fact has contributed strongly to the development of systems related to signification and sociability attached to the place.